2014
DOI: 10.1155/2014/127453
|View full text |Cite
|
Sign up to set email alerts
|

Entamoeba histolyticaandE. disparCalreticulin: Inhibition of Classical Complement Pathway and Differences in the Level of Expression in Amoebic Liver Abscess

Abstract: The role of calreticulin (CRT) in host-parasite interactions has recently become an important area of research. Information about the functions of calreticulin and its relevance to the physiology of Entamoeba parasites is limited. The present work demonstrates that CRT of both pathogenic E. histolytica and nonpathogenic E. dispar species specifically interacted with human C1q inhibiting the activation of the classical complement pathway. Using recombinant EhCRT protein, we demonstrate that CRT interaction site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…cruzi CRT to specifically bind to the C1q component of the classic pathway of serum complement in an infected host, thus inhibiting the activation of this immune response amplification system [ 47 ].The same mechanism has also been described for E . histolytica trophozoites [ 49 ]. Additionally, the interaction between C1q and trophozoites previously stimulated with Jurkat cells leads to a C1q-CRT interaction on the membrane of the trophozoites [ 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…cruzi CRT to specifically bind to the C1q component of the classic pathway of serum complement in an infected host, thus inhibiting the activation of this immune response amplification system [ 47 ].The same mechanism has also been described for E . histolytica trophozoites [ 49 ]. Additionally, the interaction between C1q and trophozoites previously stimulated with Jurkat cells leads to a C1q-CRT interaction on the membrane of the trophozoites [ 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…The immunohistochemical assays on trophozoites show that Eh CRT is in cytoplasmic vesicles and in vesicles that are in close contact with the inner cytoplasmic membrane (González et al, 2011 ). In addition, it was demonstrated that the CRT from both pathogenic E. histolytica and nonpathogenic E. dispar species specifically interact with human C1q molecules and inhibit the activation of the classical complement pathway (Ximénez et al, 2014 ). This activity is consistent with that reported by Vaithilingam et al ( 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…37 In addition, ameba developed an evasion mechanism against the host immune responses, by expressing the ER-associated calreticulin, which inhibited the classical serum complement pathway. 38 This showed that calreticulin may play a significant role in the host-parasite relationship during the early infection phases. 38 Therefore, we postulate that the increased abundance of calreticulin in the vEh variant of E. histolytica may indicate its involvement in the regulatory mechanism in relation to pathogenesis between the host and the parasite to ensure its successful survival in the host.…”
Section: Discussionmentioning
confidence: 98%